Trampoline performance under changing visual conditions - Heinen, T.; Veit, F. (Journal of Human Sport & Exercise, 2020)
Picking up and utilizing visual information is thought to be of high importance in the control of trampoline skills. Yet, the question arises how information from the different vision systems contributes to trampoline gymnastics performance. The aim of this study was to examine the role of binocular and monocular visual information in trampoline gymnastics. N = 12 gymnasts performed straight leaps on the trampoline under full vision, monocular vision, and under occluded vision. Gymnasts` preferred flight duration as well as gymnasts` variable error in feet placement on the trampoline bed were analysed by means of an optic movement analysis system. Results revealed that gymnasts exhibited longer flight duration in the binocular vision condition and the monocular vision condition, as compared to the occluded vision condition. Gymnasts furthermore exhibited a larger variable error in feet placement with less visual information available. It is argued that gymnasts benefit from the availability of binocular information in order to perform precise leaps on the trampoline. Nevertheless, it is argued that utilizing visual cues in trampoline gymnastics is likely to depend on the current configuration of task-constraints (i.e., performing straight leaps vs. somersaults with and without twists).